2013
DOI: 10.1007/s10096-013-2033-3
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and clinical symptomatology of Clostridium difficile infections in a community setting in a cohort of Danish patients attending general practice

Abstract: Clostridium difficile infection (CDI) is gradually being recognised as a cause of morbidity in the community. We investigated the incidence and clinical characteristics of CDI in a community setting and characterised the C. difficile strains by toxin gene profiling and polymerase chain reaction (PCR) ribotyping. Patients included in the study had attended general practice, primarily because of diarrhoea; CDI patients (259 patients; 121 <2 years of age) had positive cultures for toxigenic C. difficile and non-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although Dial et al 27 also used data from the UK General Practice Research Database, the authors reported that there was no overlap between this and Dial et al 25 because they used different case definitions for CDI 27 . Additionally, 2 publications (Soes et al 28 and Soes et al 29 ) reported results from the same Danish cohort. Therefore, Delaney et al 26 and Soes et al 29 were excluded from the analyses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although Dial et al 27 also used data from the UK General Practice Research Database, the authors reported that there was no overlap between this and Dial et al 25 because they used different case definitions for CDI 27 . Additionally, 2 publications (Soes et al 28 and Soes et al 29 ) reported results from the same Danish cohort. Therefore, Delaney et al 26 and Soes et al 29 were excluded from the analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 2 publications (Soes et al 28 and Soes et al 29 ) reported results from the same Danish cohort. Therefore, Delaney et al 26 and Soes et al 29 were excluded from the analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…data). Data for the Netherlands and Denmark suggest that current estimations of CA-CDI incidence are largely underestimated because of low diagnostic activity ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%